Managing the crisis among managers in the Ministries of Defense and Interior - Hussein Qassem, Hiba; Mansour Helou, Buthaina (Al-Adab Journal, 2020)
As for the concept of crisis management, the researcher prepared a measure for it, based on the theory of Moss, which he defined: “It is the employment of the individual to his adaptive strategies with the stressful situation in order to restore his psychological and social equilibrium” (Moss, 1990, p. 234), as well. On asking an exploratory question to the sample, (18) situations expressing the crisis experienced by the directors in their departments, and each situation has three methods to deal with it (cognitive, behavior, and avoidance).The researcher has verified the validity of its measurement with two indicators, which are validity by presenting the paragraphs of the scale with a questionnaire on (14) arbitrators in psychological measurement and psychology, and based on their opinions the paragraphs of the scale have been modified, and the indicator of the reliability through the correlation of the degree of the paragraph with the overall degree, and the correlation of the degree of the paragraph with the behavioral component To which it belongs, and the researcher has verified the stability of the scale by a re-test method, with an average (0.49) of the crisis management scale.After verifying the accuracy of the psychometric properties of the research tools and their paragraphs, the research tools were applied to the basic research sample of (300) director, and the data were analyzed using the statistical bag of social sciences (spss) and the results showed the following: _managers follow two methods of crisis management, namely (cognitive and behavioral) compared to the (avoidance) method.Productive-oriented managers follow the cognitive and behavioral approaches to crisis management.